REVISITING TRADITIONAL COSTING IN AGRICULTURE: A COMPARATIVE ANALYSIS OF ABC AND CONVENTIONAL METHODS - Nurma Sari; Dini Lestary; Pratiwi Kurniati; Fitri Jayanti; Dewa Ruci (E-Jurnal Akuntansi TSM, 2026)
This study aims to analyze the application of the Activity-Based Costing (ABC) method in calculating the cost of production for leading agricultural commodities in Ketapang Regency and to evaluate the effectiveness of its use through the Google Spreadsheet application. Using a qualitative descriptive approach, data were obtained through interviews, observations, and documentation involving farmers who still use traditional cost-recording systems. The findings reveal that the ABC method provides more accurate cost information compared to the single-rate system, as it considers the varying intensity of production activities such as planting, spraying, and watering. The comparison results indicate cost distortions in the traditional method, manifested as overcost and undercost, which may affect pricing and profitability. The implementation of the ABC method integrated with Google Spreadsheet has been proven to enhance efficiency, transparency, and ease of cost analysis for farmers. This study contributes to strengthening digital-based Islamic management accounting practices that are practical and applicable to the agricultural sector in rural areas.